If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + -3 = 5 + 6m Reorder the terms: -3 + 4m = 5 + 6m Solving -3 + 4m = 5 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. -3 + 4m + -6m = 5 + 6m + -6m Combine like terms: 4m + -6m = -2m -3 + -2m = 5 + 6m + -6m Combine like terms: 6m + -6m = 0 -3 + -2m = 5 + 0 -3 + -2m = 5 Add '3' to each side of the equation. -3 + 3 + -2m = 5 + 3 Combine like terms: -3 + 3 = 0 0 + -2m = 5 + 3 -2m = 5 + 3 Combine like terms: 5 + 3 = 8 -2m = 8 Divide each side by '-2'. m = -4 Simplifying m = -4
| 3x/2=6/5 | | 3(a-4)=2a+3 | | x^3-3x=100 | | A/12=7/6 | | 1/64=16^6x-7 | | 333x^2+16x-192=0 | | 7k/8-3/4-5k/16 | | 5x+0.5=2x | | 7x+3y-5x-6y= | | 3x-2+6x+4=-14+4x+8-5x-12 | | 8e+7= | | 4(3x+1)=2(5x+10) | | 24w/200 | | 5(3x+4)=15 | | x/7-8x/7 | | -7x/4=42 | | -4x/5-3=1 | | 16x+12=x+102 | | 6(x-2)-13=-55 | | 6x-30=-60 | | 13x+6=2x+72 | | (7+2x)(4-6x)=14-12x^2 | | 9x+27=-324 | | n=4n-36 | | 36x/4=-81 | | m-19=-13 | | 3x-15=-60 | | -1y+4=x | | (15/3y)-(6/2y-2) | | 3x-15/4=-15 | | 3=-2x+18 | | 4x+54=10 |